Electronic Nose and Exhaled Breath NMR-based Metabolomics Applications in Airways Disease - Santini, Giuseppe; Mores, Nadia; Penas, Andreu; Capuano, Rosamaria; Mondino, Chiara; Trové, Andrea; Macagno, Francesco; Zini, Gina; Cattani, Paola; Martinelli, Eugenio; Motta, Andrea; Macis, Giuseppe; et al. (Current Topics in Medicinal Chemistry, 2016)
Breathomics, the multidimensional molecular analysis of exhaled breath, includes analysis of exhaled breath with gas-chromatography/mass spectrometry (GC/MS) and electronic noses (e-noses), and metabolomics of exhaled breath condensate (EBC), a non-invasive technique which provides information on the composition of airway lining fluid, generally by high-resolution nuclear magnetic resonance (NMR) spectroscopy or MS methods. Metabolomics is the identification and quantification of small molecular weight metabolites in a biofluid. Specific profiles of volatile compounds in exhaled breath and metabolites in EBC (breathprints) are potentially useful surrogate markers of inflammatory respiratory diseases. Electronic noses (e-noses) are artificial sensor systems, usually consisting of chemical cross-reactive sensor arrays for characterization of patterns of breath volatile compounds, and algorithms for breathprints classification. E-noses are handheld, portable, and provide real-time data. E-nose breathprints can reflect respiratory inflammation. E-noses and NMR-based metabolomics of EBC can distinguish patients with respiratory diseases such as asthma, COPD, and lung cancer, or diseases with a clinically relevant respiratory component including cystic fibrosis and primary ciliary dyskinesia, and healthy individuals. Breathomics has also been reported to identify patients affected by different types of respiratory diseases. Patterns of breath volatile compounds detected by e-nose and EBC metabolic profiles have been associated with asthma phenotypes. In combination with other -omics platforms, breathomics might provide a molecular approach to respiratory disease phenotyping and a molecular basis to tailored pharmacotherapeutic strategies. Breathomics might also contribute to identify new surrogate markers of respiratory inflammation, thus, facilitating drug discovery. Validation in newly recruited, prospective independent cohorts is essential for development of e-nose and EBC NMRbased metabolomics techniques.
Keywords: Chronic obstructive pulmonary disease